Kinetics of photocationically curable formulations involving glycerol diglycidyl ether and phenyl glycidyl ether - Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2014)
Kinetic analysis of formulations based on glycerol diglycidyl ether and phenyl glycidyl ether were carried out in the presence of sulfonium salt as initiator at 35 mW cm(-2) using photo differential scanning calorimeter and the final conversion was found to increase with an increase in phenyl glycidyl ether content. The effects of formulation monomer ratios at three different temperatures were studied. The variations in the observed kinetic parameters can be related to increase in mobility of reactive species with temperature, distance of counter ion from the propagating cationic center, as well as extent of crosslinking reaction which controlled the course and duration of the reaction. The applicability of autocatalytic kinetic model was also evaluated and the system underwent early gelation and the activation energy decreased with an increase in phenyl glycidyl ether content. Analysis of stable photocured films containing glycerol diglycidyl ether and phenyl glycidyl ether showed better thermal stability than rigid films obtained with glycerol diglycidyl ether.
Keywords: autocatalytic kinetic model; Cationic photopolymerization; Glycidyl ether; Photo DSC